Analisis Strategi Digital Marketing Melalui Instagram dan Tiktok dalam Meningkatkan Brand Awareness Wirausaha Baru (Studi Kasus Pada Buket Bunga AR Flowerist di Desa Mbalong Kabupaten Trenggalek) - Haliza, Aulynofa Nur; Rini Ratna Nafita Sari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the growing digital era, it is important for brands to adapt to changes in consumer behavior that are more active on online platforms. Digital marketing is currently one of the important aspects for businesses in increasing brand awareness. To increase brand awareness of a product, an effective and relevant digital marketing strategy is needed, utilizing social media platforms such as Instagram and TikTok because these platforms have a wide user base. AR Flowerist has implemented a digital marketing strategy through social media platforms such as Instagram and Tiktok to introduce its products. However, these efforts have not fully increased brand awareness among consumers. AR Flowerist still faces challenges in reaching wider consumers on Instagram and Tiktok. The object of this research is AR Flowerist, a business that focuses on selling flower bouquets. The research method used is a qualitative method with data collection techniques through in-depth interviews, observation, and archival or document analysis. The results show that the implementation of digital marketing strategies by AR Flowerist on Instagram and Tiktok significantly increases brand awareness among followers, which is supported by a combination of product innovation, visual quality of content, understanding of the audience, scheduling the right posting time, and appropriate frequency and variety of content. However, obstacles faced in implementing this strategy include intense competition, limited human resources and time, lack of knowledge and skills in digital marketing, dynamic algorithm changes, and the absence of a method to measure the effectiveness of digital marketing.